Relationship between classic indicators of health behaviour and contraceptive choices in women in Flanders - Nina Van Eekert; Naomi Biegel; Leen De Kort; Veronique Verhoeven; Thies Gehrmann; Caroline Masquillier; Sarah Ahannach; Sarah Lebeer (BMC, 2024)
Abstract Background In this study we shed light on ongoing trends in contraceptive use in Flanders (Belgium). Building on the fundamental cause theory and social diffusion of innovation theory, we examine socio-economic gradients in contraceptive use and the relationship to health behaviours. Methods Using the unique and recently collected (2020) ISALA data, we used multinomial logistic regression to model the uptake of contraceptives and its association to educational level and health behaviour (N:4316 women). Results Higher educated women, and women with a healthy lifestyle especially, tend to use non-hormonal contraceptives or perceived lower-dosage hormonal contraceptives that are still trustworthy from a medical point of view. Moreover, we identified a potentially vulnerable group in terms of health as our results indicate that women who do not engage in preventive health behaviours are more likely to use no, or no modern, contraceptive method. Discussion The fact that higher educated women and women with a healthy lifestyle are less likely to use hormonal contraceptive methods is in line with patient empowerment, as women no longer necessarily follow recommendations by healthcare professionals, and there is a growing demand for naturalness in Western societies. Conclusion The results of this study can therefore be used to inform policy makers and reproductive healthcare professionals, since up-to-date understanding of women's contraceptive choices is clearly needed in order to develop effective strategies to prevent sexually transmitted infections and unplanned pregnancies, and in which women can take control over their sexuality and fertility in a comfortable and pleasurable way.